High temperature characteristics of a 2 μm InGaSb/AlGaAsSb passively mode-locked quantum well laser - Li, Xiang (2019)
A monolithic two-section InGaSb/AlGaAsSb single quantum well mode-locked laser (MLL) emitting at 2 μm is demonstrated. The laser is able to lase in the continuous wave mode up to 80 °C, and passive mode locking operation with a fundamental repetition frequency of ∼18.4 GHz is observed up to 60 °C. The laser has a characteristic temperature T0 of ∼88 K near room temperature, which is only slightly affected by the absorber bias voltage (Va). One consequence of this finding is verified by the temperature-independent power ratios before lasing. The variations of the repetition frequency with gain current (Ig) and temperature (T) have also been systematically investigated. In the bias range in this work, the repetition frequency increases as a whole by more than 30 MHz when the temperature is raised from 20 to 40 °C. Frequency tuning of ∼130 and ∼60 MHz was observed at 20 and 40 °C, respectively. The results and their mechanism analysis provide guidelines for GaSb-based MLLs to better meet the application-required repetition frequencies even with the presence of an unwanted increase in temperature.